International legal regulation of the employment of artificial-intelligence-related technologies in armed conflict - D. Lewis (Московский журнал международного права, 2020)
INTRODUCTION. In recent years, increased attention has been dedicated at the international level to legal issues concerning the possible employment of artificialintelligence-related technologies in hostilities in armed conflict. Most prominently, discussions in the framework of the Convention on Certain Conventional Weapons (CCW) have addressed juridical aspects relative to emerging technologies in the area of lethal autonomous weapons systems.MATERIALS AND METHODS. I analyze contemporary intergovernmental debates in the context of the CCW, international legal frameworks pertaining to armed conflict, and developments in relevant technologies. I do so to trace current trajectories and generate an analytical framework to help apply legal responsibility.RESEARCH RESULTS. A disagreement has arisen among certain States in the context of the CCW as to whether to develop a new primary legal norm or whether existing international humanitarian law is suffi ent. Taking account of that current normative impasse, I propose an analytical framework aimed at ensuring the applicability of international legal responsibility in respect of the employment of AI-related technologies in armed conflict.DISCUSSION AND CONCLUSIONS. Given the range of relevant technologies, the employment of AI in armed conflict may occur across diverse thematic and functional areas: not only in the conduct of hostilities, including weapons, but also detention, humanitarian services, maritime systems, and many other areas. Identification of the general concepts and specific attributes necessary to apply international legal responsibility across the array of implicated areas may help provide a framework through which to respect the law, guide behavior, pursue accountability, and generate areas of greater normative consensus.